Exploring the temporal variations in accessibility to health services for older adults: A case study in Greater London. (March 2022) - Zhang, Yuerong; Cao, Mengqiu; Cheng, Long; Gao, Xing; De Vos, Jonas
Abstract: Introduction: Increasing attention has been paid to accessibility and equity during the last two decades. Yet, despite the proliferation of studies investigating accessibility and equity from the perspective of the younger generation, only modest progress has been made in embedding a temporal perspective and targeting health services for older adults. Currently, the number of people over 60s in London is growing rapidly and is projected to increase to approximately two million by 2035. Aims: This research aims to examine walking accessibility to General Practitioners (GPs) for older people in Greater London, with a particular focus from a temporal perspective. Methods: Three different datasets were used for this study, namely: GP services data and data on GP Opening Times data from NHS Choices; the London Lower Super Output Area (LSOA) atlas; and the road network derived from OpenStreetMap (OSM). This study uses on the cumulative method to calculate accessibility to GPs – and applies the vertical equity index to measure temporal equity. Results: Our results show that opening times have a significant impact on accessibility to health services for older people in London. Overall accessibility peaked at midday when 15.88% of areas have a low degree of accessibility. Additionally, our study classifies local authorities into five groups based on their performance on accessibility and vertical equity measurements. We found several districts with inadequate and unequal accessibility that can be identified as vulnerable areas. Conclusions: Gaining insights into the temporal variations in accessibility to GPs represents a key step towards providing optimal services. Our findings can be used to provide an evidence-based reference for transport planners and policymakers to promote age-friendly development and planning. Highlights: We examine walking accessibility to General Practices for older people. Opening times have a significant impact on accessibility to health services. There are five classified groups regarding accessibility and vertical equity measurements. Several districts with inadequate and unequal accessibility have been identified. Our findings contribute and promote age-friendly development and planning.